Allergy and asthma in elite summer sport athletes - Helenius, I.; Haahtela, T. (Journal of Allergy and Clinical Immunology, 2000)
Exercise may increase ventilation up to 200 L/min for short periods of time in speed and power athletes, and for longer periods in endurance athletes, such as long-distance runners and swimmers. Therefore highly trained athletes are repeatedly and strongly exposed to cold air during winter training and to many pollen allergens in spring and summer. Competitive swimmers inhale and microaspirate large amounts of air that floats above the water surface, which means exposure to chlorine derivatives from swimming pool disinfectants. In the summer Olympic Games, 4% to 15% of the athletes showed evidence of asthma or used antiasthmatic medication. Asthma is most commonly found in endurance events, such as cycling, swimming, or long-distance running. The risk of asthma is especially increased among competitive swimmers, of which 36% to 79% show bronchial hyperresponsiveness to methacholine or histamine. The risk of asthma is closely associated with atopy and its severity among athletes. A few studies have investigated occurrence of exercise-induced bronchospasm among highly trained athletes. The occurrences of exercise-induced bronchospasm vary from 3% to 35% and depend on testing environment, type of exercise used, and athlete population tested. Mild eosinophilic airway inflammation has been shown to affect elite swimmers and cross-country skiers. This eosinophilic inflammation correlates with clinical parameters (ie, exercise-induced bronchial symptoms and bronchial hyperresponsiveness). Athletes commonly use antiasthmatic medication to treat their exercise-induced bronchial symptoms. However, controlled studies on their long-term effects on bronchial hyperresponsiveness and airway inflammation in the athletes are lacking. Follow-up studies on asthma in athletes are also lacking. What will happen to bronchial hyperresponsiveness and airway inflammation after discontinuation of competitional career is unclear. In the future, follow-up studies on bronchial responsiveness and airway inflammation, as well as controlled studies on both short- and long-term effects of antiasthmatic drugs in the athletes are needed. J Allergy Clin Immunol 2000 Sep;106(3):444-52